"It's just like a waiting room" : The experiences of psychology Honours students who are not accepted into any professional training programme for psychology in South Africa - Duiker, Adeline (Rhodes University, Faculty of Humanities, Department of Psychology)
Objective: This study explored the lived experiences of currently enrolled psychology Honours students, who are not in a professional training programme for psychology in South Africa. Method: Semi-structured interviews were conducted with eight psychology Honours students at a South African university and analysed using Interpretative Phenomenological Analysis. Findings: Findings revealed that participants perceived an Honours in psychology qualification as significant in personal capacity and insignificant in professional capacity. Additionally, findings showed that participants perceive the difficulty gaining entrance into a professional training programme and lack of employment in the field for Honours psychology graduates, as a contributing factor to several graduates being placed in a state of uncertainty, lacking professional progression in the field of psychology. Furthermore, findings revealed that several Honours psychology students battled to find employment in the field. Conclusions: I critically reflect on the implications of the findings in relation to psychology as a profession in South Africa.
Keywords: Psychology-- Study and teaching (Higher) -- South Africa; Psychology students Employment -- South Africa; Psychology students Attitudes; Psychology Practice -- South Africa; Professional associations -- South Africa; Professional education -- South Africa; Career development -- South Africa; Universities and colleges Honors courses -- South Africa; Interpretative Phenomenological Analysis